2005
DOI: 10.1158/0008-5472.can-04-1349
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Transcription from an Unrelated Promoter Can Result in MDR-1 Expression following Drug Selection In vitro and in Relapsed Lymphoma Samples

Abstract: The development of drug resistance in the treatment of cancer remains a major problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 43 publications
(38 reference statements)
0
11
0
Order By: Relevance
“…Reactivated HERVLE can modulate expression of adjacent genes. For instance, HERVLE have been shown to act as alternate promoters for varying cellular genes in Hodgkin lymphoma and Non-Hodgkin lymphoma cells ( Huff et al, 2005 ; Lamprecht et al, 2010 ; Lock et al, 2014 ; Babaian et al, 2016 ).…”
Section: Endogenous Viral Elements (Eve)mentioning
confidence: 99%
“…Reactivated HERVLE can modulate expression of adjacent genes. For instance, HERVLE have been shown to act as alternate promoters for varying cellular genes in Hodgkin lymphoma and Non-Hodgkin lymphoma cells ( Huff et al, 2005 ; Lamprecht et al, 2010 ; Lock et al, 2014 ; Babaian et al, 2016 ).…”
Section: Endogenous Viral Elements (Eve)mentioning
confidence: 99%
“…Unexpectedly, these gene hybrids differed, suggesting that ABCB 1 merely required a sufficiently active promoter to activate it and that the specific promoter was irrelevant. Other ABCB 1 mRNA hybrids have also been reported (47). These hybrids were regulated by nearby genomic sequences with similarity to a retroviral element.…”
Section: Mechanisms Of Overexpression In Multi-step Selected Cell Linesmentioning
confidence: 95%
“…Several causes such as intrinsic cancer genomic instability, epigenetic mechanisms and inflammatory stressors in the tumor microenvironment have been implicated to play a critical role in the upregulation of P-gp expression ( Figure 2) (49). Studies have demonstrated that gene rearrangements and tumor mutational burden are important mechanisms to control and modulate promoter region of abcb1 gene leading to its expression (50,51). Oncogenes such as Ras, p53, c-Raf, etc.…”
Section: P-gp: Protein Expression Structure and Functionmentioning
confidence: 99%